2015
DOI: 10.1002/wsb.523
|View full text |Cite
|
Sign up to set email alerts
|

Avian abundance and reproductive success in the intermountain west: Local‐scale response to the conservation reserve program

Abstract: Conversion of extensive shrubsteppe communities to cropland has greatly reduced the habitat available to grassland-and sagebrush-obligate birds in the Intermountain West of the United States. In Washington State, approximately 600,000 ha of converted farmland have been planted to perennial grasses, forbs, and shrubs under the Conservation Reserve Program (CRP), currently the largest-scale effort creating perennial grassland habitat in this region. From 2003 to 2005 we sampled breeding birds and vegetation char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…The high abundances of the breeding bird community at Riverby further suggested that reproduction and survival rates were also high in the restored habitats (Fletcher et al 2010;Haegen et al 2015). However, we did not assess nest success or survival in this study.…”
Section: Namementioning
confidence: 91%
“…The high abundances of the breeding bird community at Riverby further suggested that reproduction and survival rates were also high in the restored habitats (Fletcher et al 2010;Haegen et al 2015). However, we did not assess nest success or survival in this study.…”
Section: Namementioning
confidence: 91%